Turmeric as a Key Ingredient in Cosmeceuticals: New Scientific Evidence - Mohd.Wasiullah; Piyush Yadav; Yadav Swati Chandraprakash; Manyata Yadav (International Journal of Toxins and Toxics, 2024)
Turmeric (Curcuma longa), particularly its active compound curcumin, is gaining recognition in cosmetics and medicine for its therapeutic properties. Its antioxidant, anti-inflammatory, and antimicrobial effects make it a popular skincare ingredient, helping reduce inflammation, brighten skin, and fight aging. In addition to treating dandruff and promoting hair growth, Turmeric is also good for scalp health. Curcumin increases the body's antioxidant defenses. Inhibits inflammation and anti-oxidants. Curcumin, a powerful compound found in turmeric, enhances the body’s antioxidant defenses by neutralizing free radicals, reducing oxidative stress, and supporting cellular health. It also inhibits inflammation, promoting overall well-being. While some may experience mild irritation, turmeric's safety and effectiveness in both skincare and pharmaceuticals make it a promising natural solution for beauty and wellness. Turmeric’s broad versatility extends to treating conditions like acne, eczema, and wrinkles, while ongoing research is enhancing its formulation for even greater efficacy. Additionally, its anti-inflammatory and antioxidant properties contribute to its ability to soothe skin, reduce redness, and promote a healthy complexion. As more studies explore its potential, turmeric continues to gain recognition as an essential ingredient in holistic wellness and cosmetic products.As a natural powerhouse in both beauty and therapeutic treatments, turmeric is poised to lead the next wave of skincare and haircare innovation.
Keywords: Anti-inflammatory; Antiaging; NF-kB pathway; antioxidant; curcumin